2012
DOI: 10.2147/jmdh.s34447
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of an aerobic endurance test for nonexpert swimmers

Abstract: Background:This study aimed to verify the reproduction of an aerobic test to determine nonexpert swimmers’ resistance.Methods:The sample consisted of 24 male swimmers (age: 22.79 ± 3.90 years; weight: 74.72 ± 11.44 kg; height: 172.58 ± 4.99 cm; and fat percentage: 15.19% ± 3.21%), who swim for 1 hour three times a week. A new instrument was used in this study (a Progressive Swim Test): the swimmer wore an underwater MP3 player and increased their swimming speed on hearing a beep after every 25 meters. Each swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In this sense, the relative VO 2 enabled the creation of three models using BM, NLP, and AHR. These variables were selected because they are the determinants of the physiological conditions of the swimmers in the test 19,34…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this sense, the relative VO 2 enabled the creation of three models using BM, NLP, and AHR. These variables were selected because they are the determinants of the physiological conditions of the swimmers in the test 19,34…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that VO 2 max in a swimming test is obtained above the 4 minutes to meet the criteria for verification of VO 2 max (an increase of 45 mL/kg/min; rate of perceived exertion of seven, classified as “very hard;” 90% maximal heart rate) 6,27. The protocol of Veronese da Costa et al was adapted to extend the time of exercise and verification of all the criteria for reaching VO 2 max 6,19,20,26. Accordingly, the adaptation has doubled the maximum distance from 400 to 800 m, with the goal of increasing the intensity of the test with the reduction of 1 second for every two laps completed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations